2023
DOI: 10.15619/nzjp/49.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Social and technical readiness for a telehealth assessment service for adults with complex wheelchair needs: A national survey of stakeholders

Abstract: Wheelchairs can significantly improve quality of life for those who need them, yet access to physiotherapists or occupational therapists specialising in wheelchair and seating assessment can be difficult, especially for Mäori. This paper reports on a national online survey that was undertaken as phase 1 of a mixed methods study of key stakeholders of the perceived social and technical requirements of a telehealth wheelchair assessment service for people with complex mobility needs. Key stakeholders included wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Concern that a shift to telehealth delivery could exacerbate these inequities has been expressed given the social determinants of health that disproportionately affect M aori (Gurney et al, 2021) as the result of colonisation (Paradies, 2016;Reid et al, 2019). Conversely, our earlier research indicated enthusiasm for telehealth among M aori, and better technology preparedness than many other groups (Graham et al, 2021). Thus, a shift to tele-delivered intervention requires an in-depth understanding of the experiences of M aori of receiving similar services, to determine how to provide a quality, culturally appropriate service for M aori users.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Concern that a shift to telehealth delivery could exacerbate these inequities has been expressed given the social determinants of health that disproportionately affect M aori (Gurney et al, 2021) as the result of colonisation (Paradies, 2016;Reid et al, 2019). Conversely, our earlier research indicated enthusiasm for telehealth among M aori, and better technology preparedness than many other groups (Graham et al, 2021). Thus, a shift to tele-delivered intervention requires an in-depth understanding of the experiences of M aori of receiving similar services, to determine how to provide a quality, culturally appropriate service for M aori users.…”
Section: Introductionmentioning
confidence: 76%
“…Consolidated Criteria for Reporting Qualitative Research (COREQ) was met in design, analysis and reporting (Tong et al, 2007). In Phase 1, a survey identified social perspectives and technical readiness for a TWA service (Graham et al, 2021). This current Phase 2 qualitative study with a subset of survey participants enabled in‐depth and context‐specific exploration of stakeholder perceptions of a TWA service, particularly in relation to UTAUT domains of perceived effort, social influences, and facilitating conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations